Pemenuhan Hak-Hak Masyarakat Hukum Adat Dalam Investasi Pertambangan Migas Di Kabupaten Kepulauan Tanimbar - Andi Dharma Ratumasa; Teng Berlianty; Mahrita Aprilya Lakburlawal (PATTIMURA Law Study Review, 2023)
ABSTRACT: Article 33 paragraph 3 (three) of the 1945 Indonesian Constitution outlines the basic policy regarding the control and use of existing natural resources, that the earth and water and the natural resources contained therein are controlled by the State, and used to the greatest extent for the prosperity of the people. The position of customary law communities and dispute resolution within the scope of customary law communities in Maluku, Agrarian Minister Regulation Number 18 of 2019 concerning Procedures for Administering Customary Land Unity of Customary Law Peoples, administration of customary law community territories to ensure legal certainty and stipulation of recognition and protection of the unity of customary law communities. The problem approach used in this writing is the statute approach and case approach, the purpose of this paper is to know and understand the position of customary law communities in Oil and Gas Mining Law Investment in the Tanimbar Islands Regency and to know and understand the responsibilities of Business Actors in fulfilling the Rights of Customary Law Peoples in the Islands Regency Tanimbar. The type of research used is Normative Juridical with Legal Material Collection Techniques obtained from primary, secondary and tertiary legal materials, which are then analyzed based on these legal materials.Investment in oil and gas mining and processing in the territory of the lordship of customary law communities in the Tanimbar Islands district on the island of Nustual, while faced with a situation that does not have certainty for the rights of customary law communities related to the release of customary land rights which are used as a means of oil and gas mining investment. The government as an institution that has the authority to present consensus deliberations for the process of completing investment in oil and gas mining in the Masela block. as well as good responsibilities from the Inpex company as an investor. Several laws and regulations governing the position of customary law communities in the constitution of the 1945 Constitution even to Law Number 20 of 2001 concerning Oil and Gas are considered irrelevant to the development of customary law communities in the current era.